NEW TRENDS IN EUROPEAN FAMILY PROCEDURAL LAW - Drventić, Martina (EU and comparative law issues and challenges series (ECLIC), 2018)
The system of the European family procedural law is based on the multiple cross-border institutes which are developing gradually. It represents a complex system of many interrelated regulations directly regulating the cross-border family relations, through which European legislator seeks to equalize, where possible, or to connect the rules on jurisdiction and recognition, declaration of enforceability and enforcement. Also, speaking about the legal sources of the European family procedural law it is necessary to signify the interpretative power of the European Court of Justice. This paper will discuss present actuality – the Brussels IIbis Regulation Recast, respectively the Proposal COM (2016) 411/2 published by the European Commission on 30 July 2016. The proposal, in major, predicts changes regarding the rules of jurisdiction, provisional and protective measures and enforcement rules, and also introduces the new rules on incidental questions, right of the child to express his views and new rule on concentration of local jurisdiction. However, it is inevitable to raise the issue whether some other provision required changes in terms of additional explanation, referring to the rules on the transfer of jurisdiction, in the light of the new CJEU ruling in the case Child and Family Agency vs. J.D.